A public health perspective on mental health: lessons for population health in the 21st century. (23rd March 2023) - Lucey, James V.
Abstract : In December 2019, clinicians and academics from the disciplines of public health and psychiatry met in Dublin at the Royal College of Surgeons in Ireland (RCSI), to restate their shared commitment to population health. The purpose of this review is to bring our discussion to a wider audience. The meeting could not have been more timely. Six weeks later, the COVID-19 emergency emerged in China and within 12 months it had swept the world. This paper, the contents of which were presented at that meeting in December recommended that future healthcare would be guided more by public health perspectives and informed by an understanding of health economics, population health and the lessons learned by psychiatry in the 20th century. Ultimately two issues are at stake in 21 st century healthcare: the sustainability of our healthcare systems and the maintenance of public support for population health. We must plan for the next generation of healthcare. We need to do this now since it is clear that COVID-19 marks the beginning of 21 st century medicine.